2009
DOI: 10.1093/jxb/erp147
|View full text |Cite
|
Sign up to set email alerts
|

Plant-pathogen interactions and elevated CO2: morphological changes in favour of pathogens

Abstract: Crop losses caused by pests and weeds have been estimated at 42% worldwide, with plant pathogens responsible for almost $10 billion worth of damage in the USA in 1994 alone. Elevated carbon dioxide [ECO2] and associated climate change have the potential to accelerate plant pathogen evolution, which may, in turn, affect virulence. Plant–pathogen interactions under increasing CO2 concentrations have the potential to disrupt both agricultural and natural systems severely, yet the lack of experimental data and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 47 publications
(69 reference statements)
2
73
2
Order By: Relevance
“…It was proved, however, that the resistant variety was unaffected by high CO 2 , as no PM infection was detected even at EC. These findings contradict those reported for Arabidopsis by Lake and Wade (2009), who suggested that resistant ecotypes may become more susceptible to infection under EC.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It was proved, however, that the resistant variety was unaffected by high CO 2 , as no PM infection was detected even at EC. These findings contradict those reported for Arabidopsis by Lake and Wade (2009), who suggested that resistant ecotypes may become more susceptible to infection under EC.…”
Section: Discussioncontrasting
confidence: 99%
“…Investigations on powdery mildew in wheat proved that the host nitrogen content was lower at elevated CO 2 , resulting in a lower rate of infection; however, when the tissue water content was higher, the disease was more severe (Thomson et al 1993). The aggressiveness of Erysiphe cichoracearum in Arabidopsis was, however, found to increase at elevated CO 2 , as the pathogen induced morphological changes in later-formed leaves of the host plants, thus promoting the propagation of the disease (Lake and Wade 2009).…”
Section: Introductionmentioning
confidence: 98%
“…concentration provide the plant with a higher carbon/ nitrogen ratio, pathogenic plant fungi accelerate their growth and sporulation rate (Lake& Wade, 2009;Knutsen et al, 2012).Interestingly, airborne fungal spores were increased by 4-fold responding elevated CO2 concentration (Klironomos et al, 2005;Klironomos et al, 1997).…”
Section: The Impact Of Atmospheric Status (Co2 Concentration) On the mentioning
confidence: 99%
“…Plants have also shown a differential physiological response at elevated CO2 to pathogen infection; stomatal density, guard cell length and trichome number are reduced on Arabidopsis thaliana plants at elevated CO2 compared with ambient CO2 changes which potentially reduce disease susceptibility. The elevated CO2 treatments plants successfully inoculated with Erysiphe cichoracearum however exhibited an increase in the same leaf epidermal characteristics on each new leaf, enhancing disease susceptibility (Lake and Wade 2009).…”
Section: Introductionmentioning
confidence: 96%
“…These predicted changes in climate are expected to alter the potential risk of plant diseases (Sukumar Chakraborty 2011; and elicit change in host and pathogen interactions, such as an increase or decrease in disease symptoms, infection or fecundity (Lake and Wade 2009;) thus affecting crop yield and quality (Dixon 2012;Ziska et al 2004). Several of the following studies describe host-pathogen interaction under climate change but little attention is given to the underlying host-plant resistance mechanisms affected by climate change factors.…”
Section: Introductionmentioning
confidence: 99%